SEC-TAED based Error Detection and Correction Technique for Data Transmission Systems - Mr. G. Manikandan; Dr. M. Anand (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In the OFDM communication system channel encoder and decoder is the part of the architecture. OFDM channel is mostly affected by Additive White Gaussian Noise (AWGN) in which bit flipping of original information leads to fault transmission in the channel. To overcome this problem by using hamming code for error detection and correction. Hamming codes are more attractive and it easy to process the encoding and decoding with low latency. In general the hamming is perfectly detected and corrects the single bit error. In this paper, design of single Error Correction-Triple Adjacent Error Detection (SEC-TAED) codes with bit placement algorithm is presented with less number of parity bits. In the conventional Double Adjacent Error Detection (DAED) and Hamming (13, 8) SEC-TAED are process the codes and detects the error, but it require more parity bits for performing the operation. The higher number of parity bits causes processing delay. To avoid this problem by proposed the Hamming (12, 8) SEC-TAED code, it require only four parity bits to perform the detection process. Bit-reordered format used in the method increases the probability detection of triple adjacent error. It is more suitable for efficient and high speed communication.